New host records and new geographic distribution of Didymozoidae (Trematoda), parasites of Thunnus obesus (Scombridae) - Ana M. Moreira-Silva; Márcia C. N. Justo; Simone C. Cohen (Revista Mexicana de Biodiversidad)
The Scombridae fishes are of great commercial importance in Brazil, but infections caused by helminth parasites can reduce its commercial value. Thunnus obesus from the coastal zone of Rio de Janeiro was examined for helminth parasites. Three species of Didymozoidae were found: Didymocystis alalongae Yamaguti, 1938 in gill raker and operculum, Didymocystis lamotheargumedoi Kohn & Justo, 2008 associated with 3 immature forms in the operculum and Platocystis vivipara (Yamaguti, 1970) Pozdnyakov, 1987 in the skin of dorsal region. T. obesus represent new host record for Didymocystis alalongue and for D. lamotheargumedoi and Platocystis vivipara is reported for the first time in the Southwest Atlantic Ocean.